Los efectos jurídicos de las resoluciones expedidas por la Unidad de Riesgos de Trabajo de la Dirección Provincial del IESS por accidentes de trabajo en la ciudad de Riobamba, provincia de Chimborazo durante el año 2012 - Parada Boada, Ivón (2015)
ABSTRACT: This investigative work mentions occupational hazards suffered by various factors in the workplace and the legal effect of resolutions issued by the Risk Unit of the Provincial IESS, in 2012, in other words We analyze which are the most common risks to which they are subjected our employees and what are the possible solutions to prevent further accidents may even lead to death. The structure of this research is divided into four chapters: the first chapter deals with the frame of reference where the problem statement, originates its origin, as presented and how it behaves, after which formulated the general objective and specific objectives to determine if occupational risks giving rise to a legal effect on the resolutions issued by the Risk Unit Chimborazo IESS also the rationale and importance of the problem where we note that this research work is feasible, new, original and serve for both professional and nonprofessional drivers. In the second chapter the theoretical framework where the instrument of the signing was applied through which we obtained some doctrine, theories, concepts and bibliographic articles from books, laws, regulations and texts; it comes to build the theoretical, conceptual, legal part is developed and doctrinal research, this chapter is divided into four units, with its subunits. In the first unit, it talks about the risks of work, definition, generalities, types of risks in which we focus on to the research topic. The second unit will discuss factors influencing the occupational hazards in driving carefully try to conceptualize each of these factors. In the third unit will talk about some legal effects of resolutions of the unit's risk IESS? We will find what effect entails a worker who suffers an accident and what may the possible solutions, compensation be among in order to avoid civil and criminal liability. In the fourth unit, we will discuss the legal responsibility over employers at workplace accidents, which amounts to workers are entitled after to have suffered some deterioration in physical integrity, as well as civil or criminal liability of employers. It will be analyzed by a hypothetical unit, hypothesis, and cessation of variables. In the third chapter, we develop the methodological framework, through the inductive method. The use of this method will be achieved by studying problem from a particular point to an analysis of risks at work and their legal effect to make decisions by the Risk Unit of the Provincial Department of Chimborazo IESS; it includes the application of interviews to the Provincial Director of IESS, lawyers from the canton, a performance to the entire population. The interview was used with the inductive method; through the interview and the inductive method we could get the information to identify somehow the legal effect of occupational accidents. In the fourth chapter. Conclusions and recommendations were obtained from research by interpreting and discussing the achieved results its statistical tables and charts, through EXCEL. It displayed exact percentages when processing data. Consequently, this research is descriptive because it tabulates, interprets and processes information, which describes the problem as it appears. Finally, the fifth chapter holds its literature framework, supplementary literature, internet sources and Annexes.